Pengaruh Media Tumbuh Sekam Padi dan Aplikasi Limbah Cair Kelapa Sawit terhadap Pertumbuhan Stek Tanaman Kumis Kucing (Orthosiphon stamineus Benth) - Damanik, Mahrifa Fahira; Ulpah, Saripah (UIR PRESS, 2026)
This study aims to determine the interaction effect of rice husk and palm oil wastewater on the growth of cuttings of the cat's whiskers plant. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Islamic University of Riau, started from June to September 2022. This study used a completely randomized design consisting of 2 factors. The first factor was rice husk media (S), which consisted of 4 treatment levels, namely, without rice husk media, 25% rice husk media, 50% rice husk media and 75% rice husk media. The second factor was the concentration of palm oil wastewater (L) which consisted of 4 treatment levels, namely 0 ml/l water, 100 ml/l water, 200 ml/l water, and 300 ml/l water. Parameters observed were plant shoot length, shoot age, number of branches, stem diameter, total fresh weight of plants, total dry weight of plants, fresh weight of roots, and dry weight of roots. The data were analyzed statistically and continued with the honest significant difference test (HSD) at the 5% level. The results showed that the interaction between rice husk and palm oil wastewater had a significant effect on shoot length, number of branches, stem diameter, total fresh weight of plants, total dry weight of plants, fresh weight of roots and dry weight of roots. Rice husk had a significant effect on the parameters of plant shoot length, number of branches, stem diameter, total fresh weight, total dry weight, root wet weight and root dry weight with 50% rice husk. Oil palm liquid waste has a significant effect on the parameters of shoot length, number of branches, stem diameter, total fresh weight, plant total dry weight, root wet weight and root dry weight with the best concentration of palm oil liquid waste at a concentration of 200 ml/l water.